Primeira página
/
Matemática
/
Solve the equation for x: (x+3)/4-(x-2)/3=5 Type your answer below as a number (example: 5,3.1 square [+] You may submit work with your answer

Pergunta

Solve the equation for x:
(x+3)/4-(x-2)/3=5
Type your answer below as a number (example: 5,3.1
square 
[+] You may submit work with your answer

Solve the equation for x: (x+3)/4-(x-2)/3=5 Type your answer below as a number (example: 5,3.1 square [+] You may submit work with your answer

Solução

expert verifiedVerification of experts
4.1406 Voting
avatar
PedroEspecialista · Tutor por 3 anos

Responder

To solve the equation \frac{x+3}{4} - \frac{x-2}{3} = 5, follow these steps:

1. **Find a common denominator for the fractions**: The common denominator for 4 and 3 is 12.

2. **Rewrite each fraction with the common denominator**:
\frac{x+3}{4} = \frac{3(x+3)}{12} = \frac{3x + 9}{12}
\frac{x-2}{3} = \frac{4(x-2)}{12} = \frac{4x - 8}{12}

3. **Combine the fractions**:
\frac{3x + 9}{12} - \frac{4x - 8}{12} = 5
\frac{3x + 9 - 4x + 8}{12} = 5
\frac{-x + 17}{12} = 5

4. **Eliminate the fraction by multiplying both sides by 12**:
-x + 17 = 60

5. **Solve for x**:
-x = 60 - 17
-x = 43
x = -43

So, the solution to the equation is:
\boxed{-43}
Clique para avaliar: